2017
DOI: 10.4149/bll_2017_090
|View full text |Cite
|
Sign up to set email alerts
|

eNOS and XRCC4 VNTR variants contribute to formation of nicotine dependence and/or schizophrenia

Abstract: BACKGROUND: This study aimed to evaluate whether VNTR variants in the Endothelial Nitric Oxide Synthase (eNOS) and the XRCC4 gene play any role in nicotine dependence (ND) and/or Schizophrenia+ND (Sch+ND) ethiopathogenesis. METHODS: Present study included 100 individuals with ND, 60 patients with Sch+ND, and 70 healthy controls. These variants were analyzed using PCR. RESULTS: The cases with ND had higher eNOS VNTR-BB genotype than the healthy control subjects (p = 0.001). eNOS-AA genotype was lower in cases w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…However in a study investigating urothelial bladder cancer, Mittal et al found no association between XRCC4 rs6869366 variant and smoking 36 . We have previously demonstrated that XRCC4 intron 3 VNTR variant ID genotype was higher in ND group than in healthy control group 37 . In present study, we found that the frequency of XRCC4 rs6869366 GG genotype and G allele were more common in the both ND group and Sch+ND group than the control group (p = 0.001 and p = 0.001, respectively).…”
Section: Discussionmentioning
confidence: 88%
“…However in a study investigating urothelial bladder cancer, Mittal et al found no association between XRCC4 rs6869366 variant and smoking 36 . We have previously demonstrated that XRCC4 intron 3 VNTR variant ID genotype was higher in ND group than in healthy control group 37 . In present study, we found that the frequency of XRCC4 rs6869366 GG genotype and G allele were more common in the both ND group and Sch+ND group than the control group (p = 0.001 and p = 0.001, respectively).…”
Section: Discussionmentioning
confidence: 88%
“…Despite numerous studies conducted on XRCC4 variants and their association with psychiatric diseases, results remain uncertain. We also previously showed that XRCC4 intron 3 VNTR variant DD genotype was associated with schizophrenia + nicotine dependence [29]. The G1394T variant is located in the promoter region of the XRCC4 gene, and even the most subtle differences of the promoter region may regulate the biofunction of the gene product by down-regulating its expression.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the XRCC4 protein is a key component of the XRCC4/LIG4 protein complex, which allows the ends of broken DNA strands to be joined, ensuring genome integrity. XRCC4 polymorphisms have been identified and subjected to epidemiological studies to assess their potential association with predisposition to various diseases, including cancer [ 50 , 51 , 52 ].…”
Section: Polymorphism Of Genes Encoding Dna Repair Proteins In Thyroi...mentioning
confidence: 99%